Measurement of the azimuthal anisotropy of Y(1S) and Y(2S) mesons in PbPb collisions at root s(NN)=5.02 TeV - (:unkn) unknown (ELSEVIER, 2021)
The second-order Fourier coefficients (v(2)) characterizing the azimuthal distributions of Y(1S) and Y(2S) mesons produced in PbPb collisions at root s(NN) = 5.02 TeV are studied. The Y mesons are reconstructed in their dimuon decay channel, as measured by the CMS detector. The collected data set corresponds to an integrated luminosity of 1.7 nb(-1). The scalar product method is used to extract the v2 coefficients of the azimuthal distributions. Results are reported for the rapidity range vertical bar y vertical bar < 2.4, in the transverse momentum interval 0 < pT < 50 GeV/c, and in three centrality ranges of 10-30%, 30-50% and 50-90%. In contrast to the J/psi mesons, the measured v(2) values for the Y mesons are found to be consistent with zero. (C) 2021 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Heavy ion; Upsilon; Flow; PbPb; 5.02 TeV; SUPPRESSION